1933
DOI: 10.1007/bf01812175
|View full text |Cite
|
Sign up to set email alerts
|

Untersuchungen über die den Samenansatz der Luzerne beeinflussenden klimatischen Faktoren

Abstract: In einer friiheren Arbeit ,,Beitr~ge zur B1/itenbiologie der Luzerne" (7)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1935
1935
1969
1969

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…to the lodging of plants which produced much more regrowth and crowding which resulted in reduced yields. Ufer (11) has suggested that flowers from plants grown on moist soils are more difficult to trip. The work of Pedersen (2) suggests that reduced nectar secretion accompanying the reduced temperatures of the plots irrigated during blossom might retard pollination and seed setting.…”
Section: Discussionmentioning
confidence: 99%
“…to the lodging of plants which produced much more regrowth and crowding which resulted in reduced yields. Ufer (11) has suggested that flowers from plants grown on moist soils are more difficult to trip. The work of Pedersen (2) suggests that reduced nectar secretion accompanying the reduced temperatures of the plots irrigated during blossom might retard pollination and seed setting.…”
Section: Discussionmentioning
confidence: 99%
“…It seems possible that under conditions favorable for pollen collecting, there would also be a transition from the nectar tripper phase in which pollen is a by-product to a phase of purposeful collection of pollen during which nectar is gathered only at intervals. The possibility that there is a relation between the transitional phases of pollen and nectar collection and environmental factors such as relative humidity should be investigated ( 15). It is apparent that the pollen and nectar gathering activities of bees on alfalfa are• difficult to study and not yet well understood.…”
Section: Discussionmentioning
confidence: 99%